Doubled-haploid induction generates extensive differential DNA methylation in Arabidopsis. (10th October 2022) - Piskorz, Ewa W; Xu, Linhao; Ma, Yingrui; Jiang, Hua
Abstract: Doubled haploids (DHs) fix traits from hybrids in one generation. DH induction includes two changes in ploidy levels typically associated with variation in DNA methylation. However, DNA methylation patterns in DH plants and their biological significance are largely unknown. We generated three DH lines in Arabidopsis thaliana by crossing a haploid inducer with the accession Col-0, thus removing tissue culture and hybridization as a variable. DH induction produced thousands of differentially DNA methylated regions (DMRs), most of which were stochastic. Both haploidization and colchicine-induced genome duplication produced DMRs; the former mainly yielded DMRs at non-CG contexts, whereas the latter affected differential gene body methylation. Spontaneous genome doubling of haploid plants also induced DMRs in greater numbers than self-propagation. Our results provide the first evidence that haploid induction and genome doubling result in differential DNA methylation, offering a novel approach to induce epialleles. Abstract : Extensive differential DNA methylation occurs in both haploid induction and genome doubling in the process of doubled-haploid induction.